Fatal Errors: Ruth Landes and the Creation of the "Atomistic Ojibwa" - Lovisek, Joan A.; Holzkamm, Tim E.; Waisberg, Leo G. (Anthropologica, 2022)
This article examines several aspects of Ruth Landes’ depiction of the Boundary Waters Ojibwa. Based on field work in the 1930s, the "Emo" Ojibwa were characterized ahistorically by Landes as atomistic individuals living in small bands having no indigenous political organization, driven by need to disperse widely in a meagre country. Research into Landes’ published and unpublished materials, in conjunction with ethnohistorical research and Elder testimony, reveal major problems with Landes’ field work and her analysis of the Ojibwa. Although Landes’ work represents many of the biases and preconceptions of colonial anthropology, regrettably, she compromised her ethnographic portrayal by fabrications, by serious errors of fact and omission and by questionable methodology. These weaknesses limit Landes’ work as a reliable source on the Ojibwa.